Magnetic and Electrical Properties of Electrodeposited Nickel Films - Sultan, Musaab S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Magnetic and electrical properties of nickel (Ni) thin films produced by the electrodeposition technique under a range of growth times (30, 40, and 60 s) are investigated thoroughly using Magneto-Optical Kerr Effect (MOKE) magnetometry and Magneto-Resistance setup, respectively. To deeply understand these properties, the elemental composition, surface morphology, and bulk crystalline structure are analyzed using energy dispersive X-ray spectroscopy (EDS) with high-resolution scanning electronmicroscopy (HRSEM), grazing incidence X-ra y reflectivity(GIXR), and X-ray diffraction measurements, respectively. EDSanalysis confirms that these samples are free from impurities andcontamination. An increase in coercive fields ( 67 Oe) with widedistribution (58–85 Oe) across the film area and a slight variationin the shape of the loops are noticed by decreasing the film growthtime (30 s). This is attributed to the deviations in the film surfacemorphology (defects), as confirmed by HRSEM and GIXRmeasurements. The angular dependence of the coercivity is nearlyconstant for each sample and most angles, indicating the similarityin the reversal behavior in such films.The sample resistance is foundto be 20.3 Ω and 2.8 Ω for films with growth times of 40 s and 60 s,respectively. The co ercivity of the AMR profiles and MOKE loops isconsistent with each other, indicating that the magnetization at thesurface performs similarly to that of their bulks. This article givesan indication that Ni films produced by this technique under suchconditions are soft at longer deposition times and largely isotropic,which is more preferable in some magnetic applications.